Porous Media Model of Reservoir considering Seepage Stress Coupling and Seepage Field Analysis - Xu Wang; Zhenzhen Jia (Geofluids)
In the process of reservoir exploitation, the range of rock stress field changes is much larger than the reservoir area where the seepage occurs; so the amount of calculation of the existing seepage stress full coupling method is often very huge. Based on the theory of seepage mechanics and rock mechanics, a coupling analysis model of reservoir multiphase seepage and stress is established, and a numerical solution is established by using finite element and finite difference methods. The evolution law of the seepage field and stress field and the change of rock mechanics parameters can be studied, with emphasis on the readjustment of rock stress distribution and its deformation characteristics under the influence of the seepage field. At the same time, to improve the calculation efficiency of numerical simulation, considering the difference between the seepage calculation area and stress calculation area, the finite element method is improved. The percolation area of the reservoir is calculated with a fine grid to obtain a more accurate distribution of underground fluid. The coarse grid is used to calculate the stress calculation area and to reduce the calculation time. The mechanical equilibrium equation in the fully coupled theory is discretized on the coarse grid by the finite element method. The mass conservation equation is discretized on the fine grid by the finite volume method. The numerical simulation of Terzaghi’s one-dimensional consolidation problem and Mandel’s two-dimensional consolidation problem shows that the calculation results of this method are in good agreement with the analytical solution. Through the numerical calculation of a two-dimensional single-phase flow single well production problem and a three-dimensional two-phase flow five-point well pattern production problem, the influence of the seepage stress coupling effect in reservoir numerical simulation is analyzed.